The role of lithic raw materials on tool performance and use: The efficiency and durability on stone tools edge - Nora, David André Cabrita Nora (2022)
Understanding and identifying the use of stone artifacts found in the archaeological record has long been one of the main focus on the study of lithic technology. Thus, investigating the use of stone tools is critical for interpreting and reconstructing the prehistoric subsistence and behavioural patterns in archaeological investigation. The evaluation of the physical and mechanics principles underlying the question of why a particular rock type is preferred over another for the production and use of stone tools, or questions regarding the interaction between the acquisition of a particular type of lithic raw material to obtain a flake with a sharper edge was one of the main daily decision-making processes of past hominins. So, this type of action suggests predisposed know-how of lithics raw materials behave. Although not fully understood, several studies have shown that the relationship between the properties of lithic raw material and the use of stone tools has been shown to be directly related. The aim of this master's thesis is therefore to explore the interaction between the use of stone tools by prehistoric populations and their adaptability to different raw materials, using two distinguished groups coarse-grain and fine-grain rock types as main evidence. All lithic raw materials were evaluated by an experimental design regarding their efficiency and durability. At the same time, a methodology combining experimental replication and material analysis to address this issue will be presented and proposed. The controlled experimental program conducted in this thesis was designed to determine the efficiency and durability of four lithic raw materials - quartzite, flint, obsidian, and dacite. This work builds on a preliminary experiment by Pedergnana et al., 2019, which investigated the use of flint and obsidian in scraping movements. Following the initial observations made by Pedergana and colleagues, the present study aims to take the next step by introducing greater variability of raw materials and a new motion, cutting against a new contact material (wood). The experiment is conducted using a mechanical device (SMARTTESTER®) that mimics the human cutting motion, in this particular case a bidirectional longitudinal movement. The experimental plan is divided into three phases: 1) Characterization of the raw material, 2) Experiment that mimics the cutting process and quantifies the number of variables, 3) Data analysis to nullify the null hypothesis "efficiency does not vary according to the different lithic raw materials". The ability to bring new quantifiable data to consider efficiency and durability of stone tools shows that the methodology used is suitable to address these issues and can be expanded to other research questions. The results presented show that all lithic raw materials reveal their efficiency in performing a cutting movement in pine wood in the first 250 strokes. Flint proved to be the most resistant lithic raw material tested in this experiment, being the most durable and efficient after 1000 strokes. Quartzite showed a fragmentation pattern, while obsidian, being a very brittle raw material, likely shows a relationship with a technological feature in his reduction when performing bidirectional movements in wood. Dacite proved to be a good substitute for flint due to its homogeneous hardness values and consistent performance after passing through all cycles. The development of the work described in the above phases will allow to understand and quantify the efficiency and durability of each lithic raw material. These data can contribute to various topics in lithic studies, such as edge durability, reduction sequences, retouch intensity, and raw material sourcing and optimization strategies. Furthermore, this study aims to integrate a free database on an open-access platform to compare the obtained results with stone tools from other archaeological sites. As a possible case study, Kalavan 2 a Middle Paleolithic open-air site with an assemblage composed of obsidian, chert, basalt, limestone, and welded tuff associated with woodworking by use-wear studies is included in the discussion of this thesis as an example of continuous work on this topic.